Increasing Literacy and Education Beginner Voter - Dedi Kurniawan (JOELS: Journal of Election and Leadership, 2023)
General elections are a democratic process that cannot be separated from community involvement in determining legislative and executive leaders. The achievement of democracy is certainly inseparable from various elements of society, one of which is novice voters. The limitations of beginner voters to literacy and education about elections, such as not being registered in the Permanent Voter List (DPT), are a bad sign. The research conducted is field research, with a descriptive qualitative approach. The data collection technique in this research is Focus Group Discussion (FGD) with election officers and 6 Secondary Level Schools located in Siak Regency, Kandis sub-district namely Sultan Syarif Kasim SMKS, Baitul Rahman SMKS, Ponpes jabalnur, ponpes darus shofa, SMAN 3 Kandis, SMAN 1 Kandis. In Siak district there are novice voters who are classified as generation Z totaling 87. 575 (born in 1997-2012)/26.88%. The results showed that novice voters who lack literacy and education have not been selective in obtaining information about elections through various media. On the other hand, there are still beginner voters in six secondary schools who are still not registered in the permanent voter list. This shows that beginner voters who already have the right to vote can lose their right to vote due to limited information and knowledge.